Ethanol enhanced MDPV- and cocaine-induced aggressive behavior in mice: Forensic implications. (1st December 2021) - De-Giorgio, Fabio; Bergamin, Eva; Bilel, Sabrine; Tirri, Micaela; Arfè, Raffaella; Marchetti, Beatrice; Corli, Giorgia; Serpelloni, Giovanni; Marti, Matteo
Abstract: Background: Reports concerning the causal link between aggressive behavior and use and abuse of different substances (i.e., alcohol, MDPV) can be found in the literature. Nonetheless, the topic concerning the effects of acute ethanol administration on MDPV and cocaine induced aggressive behavior has yet to be thoroughly investigated. The aim of this study was to investigate such synergistic effects. Materials and methods: A total of 360 male mice were employed in the study. Ethanol was diluted with saline solution and administered 10 min before MDPV or cocaine injection via oral gavage needles. Similarly, MDPV and cocaine were dissolved in saline solution and administered by intraperitoneal injection. Different associations of specific drug doses were then tested. To investigate the acute effects of MDPV and cocaine and their interaction with ethanol on aggression in mice, a resident–intruder test was used. Results: Ethanol alone was ineffective at dosages of 0.05 g/kg and 0.25 g/kg but increased the aggressiveness of the mice at 0.125 g/kg. Similarly, the injection of both cocaine alone and MDPV alone did not significantly increase the aggressiveness of the mice; conversely, the combination of ethanol and cocaine and ethanol and MDPV enhanced aggression at specific ethanol dosages (0.05 g/kg and 0.125 g/kg). Conclusion: This study demonstrated that acute ethanol administration enhances MDPV- and cocaine-induced aggressive behavior in mice. This aggressive response is particularly enhanced when MDVP and cocaine are coupled with specific ethanol dosages, proving that psychostimulant drugs may act synergistically under certain conditions. Highlights: Acute ethanol administration enhanced MDPV induced aggressive behavior in mice. Acute ethanol administration enhanced cocaine induced aggressiveness in mice. the aggressivity caused by ethanol is increased by the intake of psychostimulants. The interaction between NPS and ethanol increase aggression in the mouse.